The Research Trends in Grammatical Arabic in the Arabic Language: a Bibliometric Review (1981-2023) - Sri Dewi Priwarti Siregar; Asep Sopian; Abdurrahman Do. Muhamad Naser (Hasanuddin University, 2023)
The bibliometric analysis will be used to examine the landscape of prior research relevant to Grammatical Arabic in Arabic from 1981 to 2023. Data were extracted from a Scopus database comprising 111 publications and improved. According to bibliometric analysis, 2022 is the year with the most article published, with 8 articles. With 35 citations, the citation trend for Grammatical Arabic in Arabic happened in 2005. With 10 publications and 5 collaboration linkages with other nations, the State of Israel became a country that published articles linked to Grammatical Arabic in Arabic. Eight of the 51 journals that publish research on this topic have been published in Q1 journals. The focus of research related to Grammatical Arabic in Arabic 1) Arabic language; 2) Natural Language Processing Systems 3) Sibawayhi.